2011
DOI: 10.1002/bab.22
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of POSS‐nanocomposite biomaterials using reactive oxygen plasma treatment for cardiovascular surgical implant applications

Abstract: In this study, central composite design (CCD) was used to develop predictive models to optimize operating conditions of plasma surface modification. It was concluded that out of the two process variables, power and duration of plasma exposure, the latter was significantly affecting the surface energy (γ(s) ), chemistry, and topography of polyhedral oligomeric silsesquioxane-poly(carbonate-urea)urethane (POSS-PCU) films. On the basis of experimental data, CCD was used to model the γ(s) using a quadratic modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 65 publications
0
51
0
Order By: Relevance
“…To create an ideal scaffold for inducing skin regeneration, it should possess excellent biocompatibility, suitable micro-pore structure (e.g., mean pore size of 100-300 m with >90% porosity), controllable biodegradability, and proper mechanical properties [37,38]. Kim et al reported the efficacy of 3D porous chitosan scaffolds for TM regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…To create an ideal scaffold for inducing skin regeneration, it should possess excellent biocompatibility, suitable micro-pore structure (e.g., mean pore size of 100-300 m with >90% porosity), controllable biodegradability, and proper mechanical properties [37,38]. Kim et al reported the efficacy of 3D porous chitosan scaffolds for TM regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The "adj R 2 " value corrects the R 2 value for the drug loading percentage and the number of terms. A high value of the The importance and effect of the factors can be determined by the sign and value of the coefficients [32,33]. Thus, the negative coefficient of A (pH) and B (time) indicates an opposite influence on DL%, while the positive coefficient of C (drug/silica) reveals the linear effect.…”
Section: Experimental Designmentioning
confidence: 99%
“…50 In a work done by Solouk et al 51 an in vitro study was carried out on human umbilical vein endothelial cells (HUVECs). The nanocomposite efficacy, safety, and compatibility with in vitro cell cultures was investigated.…”
mentioning
confidence: 99%
“…In a recent work done by Solouk et al 51 central composite design (CCD) was utilized for developing predictive models. A CCD is an experimental design, mainly used in response surface methodology, for building a second order (quadratic) model and a response variable without requiring the use of a complete three-level factorial experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation